2018
DOI: 10.1007/s10549-018-4889-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central laboratory assessments of ER, PR, HER2, and Ki67 by IHC/FISH and the corresponding mRNAs (ESR1, PGR, ERBB2, and MKi67) by RT-qPCR on an automated, broadly deployed diagnostic platform

Abstract: PurposeThe methods (IHC/FISH) typically used to assess ER, PR, HER2, and Ki67 in FFPE specimens from breast cancer patients are difficult to set up, perform, and standardize for use in low and middle-income countries. Use of an automated diagnostic platform (GeneXpert®) and assay (Xpert® Breast Cancer STRAT4) that employs RT-qPCR to quantitate ESR1, PGR, ERBB2, and MKi67 mRNAs from formalin-fixed, paraffin-embedded (FFPE) tissues facilitates analyses in less than 3 h. This study compares breast cancer biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
63
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 24 publications
15
63
2
Order By: Relevance
“… 32 In this study we underscore the significance of central Ki67 counting, which was poorly correlated with the local assessment of the marker's expression, but was found to be highly correlated with the independent automated analysis. Based on these findings and in agreement with previously published literature, 48 , 49 central Ki67 assessment should be considered as the optimal option in clinical and translational studies exploring biomarkers in BC. At the same time, digital image analysis based on this and other studies 50 could potentially become the new standard, greatly improving turnover times while simultaneously providing robust results and circumventing the known shortcomings of Ki67 assessment.…”
Section: Discussionsupporting
confidence: 85%
“… 32 In this study we underscore the significance of central Ki67 counting, which was poorly correlated with the local assessment of the marker's expression, but was found to be highly correlated with the independent automated analysis. Based on these findings and in agreement with previously published literature, 48 , 49 central Ki67 assessment should be considered as the optimal option in clinical and translational studies exploring biomarkers in BC. At the same time, digital image analysis based on this and other studies 50 could potentially become the new standard, greatly improving turnover times while simultaneously providing robust results and circumventing the known shortcomings of Ki67 assessment.…”
Section: Discussionsupporting
confidence: 85%
“…Our data over the past 2 years supports higher concordance (94%) between these methods for unselected breast cancer samples. 1113 In this study of 2018 ASCO/CAP ISH group 4 breast cancers that are difficult to classify by conventional testing, most samples also showed RT-qPCR and QIF results close to positive/negative cut points. In contrast in breast carcinomas without equivocal results by conventional testing, both RT-qPCR and QIF showed a wider range in scores further from positive/negative cut points.…”
Section: Discussionmentioning
confidence: 64%
“…Alternative methods to immunohistochemical Ki-67 assessments, such as mRNA-based analyses, were recommended in recent studies, as inter-laboratory reproducibility with ICC values of 0.980–0.998 revealed the excellent agreement of quantitative measurements for Ki-67 levels measured using MammaTyper 13,32 . Another recent mRNA-based study assessing Ki-67 levels with STRAT4 showed a good correlation with Ki-67 immunohistochemistry at a 30% cut-off 36 . However, the clinical utility, particularly in the intermediate range, has not yet been confirmed.…”
Section: Discussionmentioning
confidence: 89%